2010
DOI: 10.5194/acp-10-1649-2010
|View full text |Cite
|
Sign up to set email alerts
|

Pollution events observed during CARIBIC flights in the upper troposphere between South China and the Philippines

Abstract: Abstract.A strong pollution episode in the upper troposphere between South China and the Philippines was observed during CARIBIC flights in April 2007. Five pollution events were observed, where enhancements in aerosol and trace gas concentrations including CO, CO 2 , CH 4 , nonmethane hydrocarbons (NMHCs) and halocarbons were observed along the flight tracks during four sequential flights. The importance of the contribution of biomass/biofuel burning was investigated using chemical tracers, emission factor an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 41 publications
(63 reference statements)
7
22
0
Order By: Relevance
“…Acquisition is performed during all seasons, for a large range of solar insolation conditions, and along four main routes. In 2006 and 2007, most flights were to Manila, with two flights to South America (February (Köppe et al, 2009), season, and aircraft position relatively to the tropopause (Sprung and Zahn, 2010), and due to pollution events (Lai et al, 2010). First we briefly summarise some key results from these studies.…”
Section: Caribic Data Setmentioning
confidence: 99%
See 2 more Smart Citations
“…Acquisition is performed during all seasons, for a large range of solar insolation conditions, and along four main routes. In 2006 and 2007, most flights were to Manila, with two flights to South America (February (Köppe et al, 2009), season, and aircraft position relatively to the tropopause (Sprung and Zahn, 2010), and due to pollution events (Lai et al, 2010). First we briefly summarise some key results from these studies.…”
Section: Caribic Data Setmentioning
confidence: 99%
“…Globally, maximal values in August 2003 were found to reach 3000 pptv between 300 and 500 hPa and to reach 2000 pptv above 200 hPa (Moore et al, 2010). Lai et al (2010) showed the impact on acetone vmr of pollution events observed in the UT in April 2007. Polluted air masses crossing the flight trajectory over China led to enhancements from 350 to 1800 pptv for acetone, from 70 to 150 ppbv for CO with O 3 remaining below 100 ppbv.…”
Section: Caribic Data Setmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed ratios are similar to the air mass influenced by both fossil fuel and biofuel emissions as discussed by Lin et al (2015) over Pondicherry. Using CARIBIC observations, Lai et al (2010) also reported the CO / CO 2 ratio in the range of 15.6-29.3 ppb ppm −1 from the air mass influenced by both biofuel and fossil fuel burning in the Indochinese Peninsula. Further, the CO / CO 2 ratio is also observed at about 13 ppb ppm −1 in the south-eastern Asian outflow during February-April 2001 during the TRACE-P cam- paign and it suggests the combined influence of fossil fuel and biofuel burning (Russo et al, 2003).…”
Section: Correlation Between Co and Comentioning
confidence: 99%
“…Low values indicate more pronounced effects from respiration, fossil fuel and biomass burning. At times fresh plumes are intersected; for instance the data across biomass burning plumes over China (Lai et al, 2010) demonstrate some correlations between increases in CO and CO 2 and negative shifts in δ 13 C(CO 2 ) (data not plotted). Monsoon plumes were also crossed which were identified by increases in methane and some (negative) δ 18 O(CO 2 ) shifts.…”
Section: Variability In Co 2 and δ 13 C(co 2 ) Of Tropospheric Air Mamentioning
confidence: 99%